Women's Role Repositioning in Security Sector - Dewanto, Helmy Suryo; Hanita, Margaretha; Anriani, Stepi (Interdisciplinary Social Studies, 2023)
Background: The world of intelligence and security is still seen as the realm of men, due to the strong patriarchal culture and existing stigma, the world of intelligence and security is seen as a world that requires physical abilities, mental resilience, aggressiveness, which are considered to be more owned by men. Aim: This research is intended to describe the role of women in the intelligence and security sector, the obstacles and constraints for female officers to be more involved in intelligence and national security activities, and the importance of repositioning the role of women in fields that are still often seen as a male world. Method: This study used a qualitative research method by conducting literature studies, observing in the field, and collecting data related to this research. Findings: Awareness about the role of women in the security sector such as intelligence, law enforcement, military, needs to be continuously disseminated to all parties, not only to policy makers, organizational leaders, men, or the community, but also to women themselves so that they are not skeptical of their ability to assume a more strategic role in the sector.